The Effectiveness of Demak Regency Spatial Planning Policy through the Role of a Notary as An Official who Makes Land Deeds - Kusriyah, Sri; Witasari, Ariyani; Listyowati, Peni Rinda; Rodhiyah, Siti (Sultan Agung Notary Law Review, 2024)
Demak Regency asone of the autonomous regions has authority derived from Law No. 26 of 2007 concerning Spatial Planning, the authority for spatial planning is regulated in Article 11 that: the authority of the district/city regional government in implementing spatial planning includes: a. regulation, guidance and supervision of the implementation of the planning district/city regional space and district/city strategic areas.This writing aims to find out what the Spatial and Regional Planning Policy is related to Space Utilization in Demak Regency and how effective the Spatial Utilization policy is through the role of Notaries as Officials Making Land Deeds. The method used is a sociological juridical approach, the data used is primary data and secondary data, the theory used to analyze the problem is the theory of authority and the theory of effectiveness. The research results show 1. Space utilization in Demak district, namely: 1) Land use in Demak district is rice fields (58.79%). Non-paddy agricultural land consisting of fields/gardens, ponds and community forests occupies 23.13% of the total area, while the remainder (18.08%) is used for housing, industry, trade and offices as well as other public infrastructure. 2) Regional development, one example of developing industrial designated areas as referred to in article 64 of the 2011 Demak Regency RTRW Regional Regulation. Industrial designated areas are mostly in Demak Regency with an area of approximately 7,646 ha. The largest industrial area allocation is in Sayung and Karangtengah sub-districts because it is a top priority in the National Industrial Development Master Plan. 2. The effectiveness of Spatial Planning policies in Demak Regency through the role of the notary as PPAT, carried out in procedures for making authentic deeds related to land, must go through technical considerations for the activity of issuing suitability of space utilization activities issued by the Demak Regency Land Office and Approval of Space Utilization Activities. issued by the Peran Demak district government through the One Stop Investment and Integrated Services.